Estimativa da recarga aquífera na Bacia do Rio Riachão, MG - Lilian Catone Soares (2012)
This study was conducted in Riachão River basin, northern Minas Gerais. The region is part of the geological context of the São Francisco Craton and covers Neoproterozoic carbonate rocks alternating with terrigenous rocks of Bambuí Group, and Late Cretaceous sandstones Urucuia Group. These rocks characterize a fissure-karst and granular hydrogeological systems, respectively. The basin is characterized by a history of shortage and conflict over water use. The main objective of the study was recharge water estimation through different methods: Water Budget, Meyboom, Stream Base Flow as a Proxy for Recharge, Water Table Fluctuation (WTF) and APLIS. Recharges rates of precipitation estimated by Meyboom, Stream Base Flow as a Proxy for Recharge and WTF methods was considered low (between 2 and 8%) and recharges rates estimated by Water Budget method and APLIS method was considered medium (2 to 27 %) and high (25 to 45%), respectively. The application of different methods allowed the estimation of a minimum recharge rate expected for the area, as well as a maximum potential, and evaluation of advantages and limitations of each method.